SEMIOTIKA HORROR DALAM POSTER FILM - Widya Nirmalawati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2008)
Poster is one of the media used by an industry to market the movie products to the publics. It functions to give a preview to the potential audiences about the content or the story in a movie. In 2000s, horror movies became the popular genre produced. Many directors compete to create the most scary. This article explores the messages of horror as reflected from the poster of the movie. It is also try to compare the way the horror is packaged through poster between the eastern culture and the western culture. This is done by applying Pierce’s theory of sign.